Increasing The Role of Parents Recipients of The Family Hope Program Through a Socialization Management Strategy for The Indonesia Smart Card Scholarship Program for Studying at The International Institute of Science and Business Singkawang - Syska Gloria; Kasnur Saputra; Sutarto Sutarto; Yohanes Gala Araftake Blikololong; Legawa Tegar Ramadhan; Sofia Nur Haviza (International Journal of Public Devotion, 2025)
This Community Service Activity aims to increase the role of parents of The Family Hope Program recipients in supporting their children to access higher education through The Indonesia Smart Card Scholarship Program at The International Institute of Science and Business Singkawang. The partners of this activity overcome the problem of low understanding of parents regarding the flow and requirements for applying for The Indonesia Smart Card, which has impacts on the minimal participation of students from The Family Hope Program families in continuing their higher education. The methods used include a socialization management strategy approach through mapping information needs, compiling contextual materials, and implementing socialization in the form of lectures, discussions, and practical simulations. This activity was carried out in Bukit Batu Village, Singkawang City involving 27 participants. The results showed a significant increase in participant understanding, which was initially only 40.7% understanding The Indonesia Smart Card program before the activity, increasing to 88.9% afterwards. Supporting factors for involvement include the active involvement of The Family Hope Program facilitators, participant enthusiasm, and  communicative delivery formats. The main obstacles are limited digital literacy and implementation time. This activity promises a program in the form of continued assistance and the development of simple and easily accessible digital information mediaPeningkatan Peran Orang Tua Penerima Program Keluarga Harapan (PKH) Melalui Strategi Manajemen Sosialisasi Program Beasiswa Kartu Indonesia Pintar (KIP) Kuliah di Institut Sains dan Bisnis Internasional SingkawangABSTRAKKegiatan Pengabdian kepada Masyarakat ini bertujuan untuk meningkatkan peran orang tua penerima Program Keluarga Harapan (PKH) dalam mendukung anak-anak mereka mengakses pendidikan tinggi melalui program beasiswa Kartu Indonesia Pintar (KIP) Kuliah di Institut Sains dan Bisnis Internasional (ISBI) Singkawang. Mitra kegiatan ini menghadapi masalah rendahnya pemahaman orang tua terhadap alur dan syarat pengajuan KIP Kuliah, yang berdampak pada minimnya partisipasi siswa dari keluarga PKH dalam melanjutkan pendidikan tinggi. Metode yang digunakan meliputi pendekatan strategi manajemen sosialisasi melalui pemetaan kebutuhan informasi, penyusunan materi yang kontekstual, serta pelaksanaan sosialisasi dalam bentuk ceramah, diskusi, dan simulasi praktik. Kegiatan ini dilaksanakan di Kelurahan Bukit Batu, Kota Singkawang dengan melibatkan 27 peserta. Hasil menunjukkan peningkatan signifikan dalam pemahaman peserta, yang semula hanya 40,7% memahami program KIP Kuliah sebelum kegiatan, meningkat menjadi 88,9% setelahnya. Faktor pendukung keberhasilan meliputi keterlibatan aktif pendamping PKH, antusiasme peserta, dan format penyampaian yang komunikatif. Adapun hambatan utama adalah keterbatasan literasi digital dan waktu pelaksanaan. Kegiatan ini merekomendasikan keberlanjutan program berupa pendampingan lanjutan serta pengembangan media informasi digital sederhana dan mudah diakses.Kata Kunci:Kartu Indonesia Pintar; Program Keluarga Harapan; strategi manajemen sosialisasi; pendidikan tinggi